Early detection of chronic kidney disease using machine learning - Abrar, Tahmid; Tasnim, Samiha; Hossain, Md. Mehrab (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.